Sosialiasi Penggunaan Model Pembelajaran Mind Mapping Dalam Pembelajaran Ilmu Pengetahuan Sosial - Abdussalam, Abdussalam; Pratiwi, Siska; Firmansyah, Ihwan; Andriani, Miranti Widi (STAI Publisistik Thawalib Jakarta, 2023)
The purpose of the service is to socialize the use of the mind-mapping learning model in social studies learning content. Method of implementation with lectures and discussions. Stages of implementation: preparation, implementation, and evaluation. Equipment: laptop, LCD projector, and consumption. Participants: school principals and teachers. Implementation results: the implementation of the socialization was successful through the provision of material on the use of mind mapping models and procedures for using mind mapping models. Implementation of socialization can provide a choice of solutions to solve problems in learning activities by applying the mind-mapping learning model. Socialization activities can facilitate increasing understanding of the use of learning models by educators of the Technical Implementation Unit of the Gili Anyar Bangkalan Public Elementary School Service.